Analgesic efficacy of theta-burst stimulation for postoperative pain. (May 2023) - Cheng, Ming; Che, Xianwei; Ye, Yang; He, Changlin; Yu, Liang; Lv, Yating; Fitzgerald, Paul B.; Cash, Robin F.H.; Fitzgibbon, Bernadette M.
Highlights: We evaluated the efficacy of intermittent theta-burst stimulation (iTBS) in postoperative care across two cortical targets. iTBS reduced anaesthetic pump attempts. This effect was unique to DLPFC stimulation while M1 had no effect. Abstract: Objective: Repetitive transcranial magnetic stimulation (rTMS) may be a relevant method to assist postoperative pain. However, studies to date have only used conventional 10 Hz rTMS and targeted the DLPFC for postoperative pain. A more recent form of rTMS, termed intermittent Theta Burst Stimulation (iTBS), enables to increase cortical excitability in a short period of time. This preliminary double-blind, randomised, sham controlled study was designed to evaluate the efficacy of iTBS in postoperative care across two distinct stimulation targets. Methods: A group of 45 patients post laparoscopic surgery were randomised to receive a single session of iTBS over either the dorsolateral prefrontal cortex (DLPFC), primary motor cortex (M1), or Sham stimulation (1:1:1 ratio). Outcome measurements were number of pump attempts, total anaesthetic volume used, and self-rated pain experience, assessed at 1 hour, 6 hours, 24 hours, and 48 hours post stimulation. All randomised patients were analysed (n = 15 in each group). Results: Compared to Sham stimulation, DLPFC-iTBS reduced pump attempts at 6 (DLPFC = 0.73 ± 0.88, Sham = 2.36 ± 1.65, P  = 0.031), 24 (DLPFC = 1.40 ± 1.24, Sham = 5.03 ± 3.87, P  = 0.008), and 48 (DLPFC = 1.47 ± 1.41, Sham = 5.87 ± 4.34, P  = 0.014) hours post-surgery, whereby M1 stimulation had no effect. No group effect was observed on total anaesthetics, which was mainly provided through the continuous administration of opioids at a set speed for each group. There was also no group or interaction effect on pain ratings. Pump attempts were positively associated with pain ratings in the DLPFC ( r  = 0.59, P  = 0.02) and M1 ( r  = 0.56, P  = 0.03) stimulation. Conclusions: Our findings show that iTBS to the DLPFC reduces pump attempts for additional anaesthetics following a laparoscopic surgery. However, reduced pump attempts by DLPFC stimulation did not translate into a significantly smaller volume of total anaesthetic, due to the continuous administration of opioids at a set speed for each group. Significance: Our findings therefore provide preliminary evidence for iTBS targeting the DLPFC to be used to improve postoperative pain management.